PENDIDIKAN MULTIKULTURAL BERBASIS KARAKTER KEINDONESIAAN PADA PENDIDIKAN ANAK USIA DINI UPAYA INTEGRASI ILMU KE-ISLAMAN DAN KARAKTER KEBUDAYAAN INDONESIA (Studi Kasus di Sanggar Anak Alam Yogyakarta) - Atik Wartini (Lembaga penelitian dan pengabdian kepada masyrakat, 2015)
This paper is based on field research studies (field research) This paper considers the characteristics of Multicultural Education keindonesiaan Character Based on Early Childhood Education. This research is very interesting because of Multicultural Education keindonesiaan assessed on the basis of character, where the Indonesian people should have the character of Indonesian-ness. Furthermore, the character keindonesiaan need to be applied early, particularly in early childhood education institutions. Furthermore, this study is a description of the type of research with a qualitative approach. Data were obtained through interviews, observation and documentation. In this paper, there are three first question, how the concept of Character Based Multicultural Education ?, keindonesiaan according SALAM second, how the basic principles of learning model development on Multicultural Education keindonesiaan Character Based on SALAM ?. Third, how the implementation of Character-based Multicultural Education keindonesiaan at SALAM?. Then produced a couple of things: first, to know the concept of Multicultural Education keindonesiaan Character Based on ECD at SALAM. Second, to determine the basic principles of learning model development on Multicultural Education keindonesiaan Character Based on early childhood in SALAM, third and to know the implementation of Multicultural Education keindonesiaan Character Based on ECD at SALAM